Cover Feature: Hydrogenolysis of Furfuryl Alcohol to 1, 2‐Pentanediol Over Supported Ruthenium Catalysts (ChemistryOpen 8/2021). Issue 8 (5th August 2021) - Yamaguchi, Aritomo; Murakami, Yuka; Imura, Tomohiro; Wakita, Kazuaki
Abstract : The Cover Feature shows the conversion of furfuryl alcohol, which can be obtained from biomass, to 1, 2‐pentanediol. 1, 2‐Pentanediol is used as an antimicrobial agent and as a moisturizing ingredient in cosmetics. We found that hydrogenolysis of furfuryl alcohol over Ru/MgO at 463 K in water afforded 1, 2‐pentanediol with 42% selectivity. More information can be found in the Full Paper by Aritomo Yamaguchi et al .